The miracle of the cruse of oil. The metamorphosis of a legend - Noʿam, Ṿered (Hebrew Union College annual / Jewish Institute of Religion, 2002)
A popular view among historians considers the famous Hanukkah story of the cruse of oil, which appears in the Talmud and seemingly also in the Scholium of Megillat Taʿanit, as evidence of the determination of the Sages to erase the memory of the Hasmoneans. A careful examination of the traditions about Hanukkah in the Scholium of Megillat Taʿanit demonstrates, however, that the story, as it appears in the Babylonian Talmud, is a secondary form. The two extant versions of the Scholia offer different traditions in explaining the celebration of Hanukkah. Scholium O makes no mention of finding any oil and offers other reasons for the establishment of the festival. Scholium P does present, among other traditions, an early version of the story, which does not mention any miracle with regard to the finding of the oil. This same episode appears later in the Babylonian Talmud after it had evolved and crystallized, and when all other traditions had been rejected. The Babylonian Talmud is, in fact, the only source for the legend of the bit of oil that lasted eight days. The supernatural basis of this story, as well as its introduction as the only explanation for the celebration of Hanukkah, is a Babylonian manipulation, motivated by literary rather than historical purposes.